2023
DOI: 10.3389/fpsyg.2023.1243598
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gratitude interventions on patients with cardiovascular disease: a systematic review

Xiaoxiao Wang,
Chunli Song

Abstract: Positive psychological factors play a pivotal role in improving cardiovascular outcomes. Gratitude interventions are among the most effective positive psychological interventions, with potential clinical applications in cardiology practice. To better understand the potential clinical effects of gratitude interventions in cardiovascular disease, four databases (Web of Science, Scopus, PubMed, and PsycArticles) were searched from 2005 to 2023 for relevant studies. Randomized controlled trials of gratitude interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found that psychiatric disorders are associated with the occurrence of CVD, and may be the cause of some CVDs, positive psychological factors play a pivotal role in improving cardiovascular outcomes [23,24] . Therefore, our research based on the idea of psycho-cardiology, implementing mind-body interventions, which actively guides patients to carry out early rehabilitation activities, combined with music mindfulness meditation, respiratory training, ACP to help patients promotes mental health and adherence to healthy behaviors, improves cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that psychiatric disorders are associated with the occurrence of CVD, and may be the cause of some CVDs, positive psychological factors play a pivotal role in improving cardiovascular outcomes [23,24] . Therefore, our research based on the idea of psycho-cardiology, implementing mind-body interventions, which actively guides patients to carry out early rehabilitation activities, combined with music mindfulness meditation, respiratory training, ACP to help patients promotes mental health and adherence to healthy behaviors, improves cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%